MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS VIII-2 SMP NEGERI 1 SEI BINGAI TAHUN PELAJARAN 2018-2019 - Marni Kemit (Universitas Islam Islam Sumatera Utara, 2021)
This research is a type of Class Action Research (PTK) that aims to improve the activeness and learning outcomes of IPS students of grade VIII-2 smp Negeri 1 Sei Bingai Year 2018-2019 through the application of problem-based learning models. Grade VIII-2 students numbered 32 students with a total of 14 male students and 18 female students. This research method uses research methods from Kemmis and Taggart consisting of 4 main components, namely planning, implementation of actions, observations and reflections. Data collection techniques used are tests, observations and documentation. Ice instrument used is a test instrument problem in the form of multiple choice questions and essay questions and observation sheets consisting of indicators of student learning activity. The data is descriptively quantitative and presented in the form of tables and drawings/charts. The data from the study showed that the data on pre-cycle completion percentage by 46.8% increased in cycle I to 84.3% and reached 93.8% in cycle II. In addition to the learning outcomes, students' learning activity also increases every cycle where in cycle I the learning capacity is in the Good category and in cycle II increases to the very Good category. For the activeness of learning students also in cycle I get a good category and increase in cycle II into an excellent category. Based on these results, it was concluded that by applying a problem-based learning model, the activeness of learning and the results of ips learning of grade VIII-2 students of SMP Negeri 1 Sei Bingai Tahunn in 2018-2019 have improved.